On-treatment Modified Glasgow Prognostic Score Provides Predictive Information Complementary to Radiological Staging in Metastatic Urothelial Carcinoma on Immunotherapy. - Saal, Jonas; Grünwald, Viktor; Bald, Tobias; Ritter, Manuel; Brossart, Peter; Tomita, Yoshihiko; Hartmann, Arndt; Hölzel, Michael; Eckstein, Markus; Klümper, Niklas (European Urology Oncology, 2024)
In the immunotherapy era it is difficult to predict patient prognosis on the basis of radiological staging alone, especially for the subgroup with stable disease (SD), which encompasses a wide range of clinical outcomes. Thus, there is need for reliable and, ideally, cost-efficient biomarkers to improve the accuracy of outcome prediction. We evaluated the on-treatment modified Glasgow Prognostic Score (mGPS)-a known predictor of outcomes in several cancers that is based on serum C-reactive protein and albumin-in patients with metastatic urothelial carcinoma (mUC) treated with immune checkpoint inhibition (ICI) in the phase 2 IMvigor210 and phase 3 IMvigor211 trials. On-treatment mGPS provides valuable prognostic information complementary to radiological staging, particularly for patients with SD. In IMvigor210, on-treatment mGPS predicts outcomes as early as 6 wk after ICI initiation, considerably before the first routine staging typically performed after 10-12 wk. Our study suggests that on-treatment mGPS complements radiological imaging in predicting outcomes for patients with mUC undergoing ICI. PATIENT SUMMARY: For patients with metastatic bladder cancer receiving immunotherapy, it is difficult to predict treatment outcomes from imaging scans alone. Our study results suggest that a score called the modified Glasgow Prognostic Score based on just two proteins (C-reactive protein and albumin) measured in blood can accurately predict outcomes. Use of the mGPS along with imaging scans may be better in predicting the survival benefit from immunotherapy.
EVALuna2:548114